1984
DOI: 10.1111/j.1399-3054.1984.tb05897.x
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient translocation pattern and accumulation of free amino acids in rice coleoptile elongation under anoxia

Abstract: Menegus, E, Brambilla, I. and Bertani, A. 1984. Nutrient translocation pattern and accumulation of free amino acids in rice coleoptile elongation under anoxia -Physiol. Plant. 61: 203-208.Comparing nutrient translocation to the rice {Oryza sativa L. var. Arborio) shoot during anoxia with the aerobic situation, it was found that anoxia reduced the translocation of K+, phosphorus, Mg2+ and Ca-+ with progressive intensity; Ca^* translocation was practically zero in the absence of oxygen. The translocation of K+ a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
2

Year Published

1985
1985
2000
2000

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 20 publications
1
29
2
Order By: Relevance
“…It has been shown that rice coleoptiles steadily accumulate soluble organic phosphates throughout a 48 h period of anoxia [3]. Following the 3'P NMR study of extracts of these compounds from rice shoots, we can report that anoxia induces significant changes in the phosphodiester region of the 31P NMR spectrum, with a marked increase of the GPC level.…”
Section: Introductionmentioning
confidence: 94%
See 3 more Smart Citations
“…It has been shown that rice coleoptiles steadily accumulate soluble organic phosphates throughout a 48 h period of anoxia [3]. Following the 3'P NMR study of extracts of these compounds from rice shoots, we can report that anoxia induces significant changes in the phosphodiester region of the 31P NMR spectrum, with a marked increase of the GPC level.…”
Section: Introductionmentioning
confidence: 94%
“…It has been shown that growth, in the anoxic rice shoot, is confined to the coleoptile and is due to enlargement of existing cells along the shoot axis [3,15]; in that situation cells may be considered as oblate spheroids. For solids of this type the increase in surface area, after a major axis increase, is linearly correlated with the volume increase and is maximal for a given increase in volume, as compared to the case of spherical solids [16].…”
Section: Changes In Gpc and Other Phosphodiester Concentrations Undermentioning
confidence: 99%
See 2 more Smart Citations
“…Coleoptile elongation is sustained by the continuous translocation of carbohydrates, amino acids, and salts from the endosperm (Menegus et al, 1984;Reggiani et al, 1995;Bertani et al, 1997). Perata et al (1992) reported that rice is able to germinate in anoxic conditions because it successfully produces a-amylase even under anaerobic conditions.…”
mentioning
confidence: 99%